Congenital cystic adenomatoid malformation of the lung (CCAM): Report of 2 atypical cases - Melinda D. Nataprawira; Cissy B. Kartasasmita; 0ma Rosmayudi; Abdulgani H.; Soebarna R.; Tri Wahyu; L. Silitonga; B. Hernowo (Indonesian Pediatric Society, 1999)
Congeni cystic adenomatoid malformation (CCAM) presents mainly inneonates, rarely in children beyond infancy, and has been reported in adults. Two females (aged 26 months and 34 days) who had CCAM in the right and left lower lobe, respectively, are reported. One of them presented with recurrent respiratory infection and the other as newbom with respiratory distress secondary to mediastinal displacement and pulmonary compression as a result of expanding cystic lesions. Both cases had different lesions from typical neonatal cases reported in the literature.Single cyst was shown in the first case, but multiple cysts in other. The young child survived, but the baby died. All lesions had lining varied from pseudostratified columnar to cuboidal epithelium. Cartilage plates was found in the second case but not in the first. The absence of inflammation is typical in neonates' lesions, by contrast, all of our two patients had clinical and pathologic evidence of chronic inflammation. CCAM may be clinically silent in infancy and may present as pneumonia associated with cystic lesion on chest X-ray in childhood or la ter in life. To support the diagnosis, CT scanning is needed.